Pengaruh Pengetahuan, Sikap dan Perilaku Masyarakat Tehadap Kegiatan Urban Farming - Ulfa, Tenri; Pertiwi, Nurlita (UNM Environmental Journals, 2020)
This study describes the behavior of urban farming (UFB) in the people of Makassar City and the factors that influence it. The selection of locations and respondents was based on residential areas located in the city center and in areas outside the city with the community carrying out urban farming activities, as many as 50 respondents. The type of research is descriptive quantitative and correlational using a questionnaire instrument analyzed with descriptive statistical techniques and a comparison test with Kendall's test. The results of the study indicate that respondents generally have high environmental knowledge, while respondents' environmental attitudes are in the moderate category. The reasons for urban farming as a lifestyle were revealed to 27 respondents with high urban farming behavior. Meanwhile, there were 23 respondents with low urban farming activities who revealed the difficulties in implementing urban farming due to time constraints. The results of statistical analysis show that there is a significant (significant) relationship, which is strong and unidirectional in all of the good relationships between knowledge and attitudes, knowledge with behavior and attitudes with behavior, this means that the higher knowledge will affect the attitudes and behavior of respondents, so also with a change in attitude will have an impact on the behavior of respondents in terms of carrying out urban farming activities.